Analysis of Export Competitiveness of Natural Rubber from Indonesia and Thailand in the International Market - Mustafa Usman; Mita Rezekina U; Akhmad Baihaqi; Srihandayani (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2021)
Natural rubber is one of the commodities that plays an important role as a foreign exchange earner. This study aims to determine how the competitiveness of natural rubber in Indonesia and Thailand as the main producers in the world market. The data used in this study is the volume of exports and imports of natural rubber in Indonesia and Thailand for 15 years in the 2004-2018 period. This research uses Revealed Comparative Advantage (RCA) analysis to analyze comparative advantage and Trade Specialization Index (ISP) to analyze competitive advantage. The RCA analysis results in world markets, the United States market and the Chinese market show a number of more than 1 which means that natural rubber in Indonesia and Thailand have strong competitiveness or comparative advantage. However, in the world market and the United States market the value of the Indonesian natural rubber RCA index is higher than the Thai RCA index value so that the competitiveness of Indonesia's natural rubber is stronger than Thailand, while in the Chinese market the value of the Thai RCA index is the opposite. Indonesia and Thailand ISP Index values show positive results, indicate that these two countries have a tendency to be an exporter of natural rubber commodity in the world market, the American market, and the Chinese market.